Analisis Kebijakan Makroekonomi di Masa Ketidakpastian Global terhadap Daya Beli Indonesia - Lestari Sihite; Ayu Angelina; Hasanah Hasanah (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to analyze the impact of macroeconomic policies, specifically global oil prices, the BI Rate, and government expenditure, on inflation and its implications for the purchasing power of the Indonesian people amid global uncertainty. Utilizing a quantitative approach with a descriptive-associative design, this research utilizes monthly time series data from January 2015 to December 2024. The analytical method applied is the Error Correction Model (ECM) with the two-step Engle Granger procedure. The estimation results indicate that global oil prices have a positive and significant effect on inflation in both the short and long term, demonstrating a direct transmission of cost-push inflation that threatens real purchasing power. Meanwhile, the BI Rate also shows a strong positive and significant influence in both models, reflecting a proactive (forward-looking) monetary policy response where interest rates are raised to anchor inflation expectations driven by external shocks. Conversely, government expenditure consistently has no significant effect on inflation, indicating that inflation in Indonesia during the observation period was driven by global supply shocks rather than domestic demand-pull inflation. Furthermore, the short-term Error Correction Term (ECT) coefficient is positive and significant, indicating a divergent or over-correction effect in the short term due to the internal lag autocorrelation of inflation itself.